Bipolar disorder vulnerability : perspectives from pediatric and high-risk populations - Soares, Jair C.; Walss-Bass, Consuelo; Brambilla, Paolo (Academic Press, an imprint of Elsevier, 2018)
Bipolar Disorder Vulnerability: Perspectives from Pediatric and High-Risk Populations synthesizes our current understanding of high-risk and pediatric populations to aid readers in identifying markers of vulnerability for the development of bipolar disorder, with an ultimate goal of the development of drug targets and other therapies for early diagnosis and treatment. The book provides readers with an understanding of biological and environmental factors influencing disease manifestation that will aid them in defining discrete clinical stages and, importantly, establish an empirical basis for the application of novel therapeutics in a phase of illness during which specific treatments could more effectively alter disease course. Whereas most of the literature available on the pathophysiological mechanisms of bipolar disorder focuses on chronically ill adult individuals, this represents the only book that specifically examines pediatric and high-risk populations. An estimated 30 to 60 percent of adult bipolar disorder patients have their disease onset during childhood, with early-onset cases representing a particularly severe and genetically loaded form of the illness. Highlights diverse translational methodologies, including functional and structural neuroimaging, neuropsychological testing and integrated genomicsExamines molecular trajectories in youth with bipolar disorder and unaffected youth at high risk for developing bipolar disorderExplores the interaction between genomic and environmental influences that shape behavior